2023
DOI: 10.1057/s41599-023-01705-y
|View full text |Cite
|
Sign up to set email alerts
|

Profiling low-proficiency science students in the Philippines using machine learning

Abstract: Filipino students’ performance in global assessments of science literacy has always been low, and this was confirmed again in the PISA 2018, where Filipino learners’ average science literacy scores ranked second to last among 78 countries. In this study, machine learning approaches were used to analyze PISA data from the student questionnaire to test models that best identify the poorest-performing Filipino students. The goal was to explore factors that could help identify the students who are vulnerable to ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…The poor outcome in the performance level across cognitive skills aligns with the research conducted by Bernardo et al (2023), which found that Filipino students' performance on PISA 2018 is complemented by another international assessment, the Trends in International Mathematics and Science Study (TIMSS). This assessment measures students' ability to apply their knowledge in various content areas in science.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The poor outcome in the performance level across cognitive skills aligns with the research conducted by Bernardo et al (2023), which found that Filipino students' performance on PISA 2018 is complemented by another international assessment, the Trends in International Mathematics and Science Study (TIMSS). This assessment measures students' ability to apply their knowledge in various content areas in science.…”
Section: Discussionsupporting
confidence: 76%
“…The results of the study are supported and has similarities with the research study of Bernardo et al (2023) as they unearth the results of PISA 2018 that the performance for Filipino students for global assessments has always been significantly low in performance of science. This means that the average of Filipino learners in scientific literacy ranked second to last among 78 countries.…”
Section: Discussionsupporting
confidence: 74%
“…Through the voices of educators at St. Michael's College, Iligan City, the researcher unravels the intricate process of adapting to AI-infused educational landscapes (Gašević et al, 2023). The stories of educators navigating these uncharted waters provide insights that inform the development of meaningful and impactful training programs, thereby enhancing the potential of AI to catalyze transformative learning experiences (Bernardo et al, 2023).…”
Section: Teacher Training For Ai Integrationmentioning
confidence: 99%
“…Deep learning has played a significant role in advancements in fields such as medical computer vision 15 20 and, more recently, in large foundation models 21 – 24 . Although machine learning methods have significantly transformed various disciplines, their application in education remains relatively unexplored 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%